2009
DOI: 10.1186/1750-1326-4-55
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic low dose rotenone treatment on human microglial cells

Abstract: BackgroundExposure to toxins/chemicals is considered to be a significant risk factor in the pathogenesis of Parkinson's disease (PD); one putative chemical is the naturally occurring herbicide rotenone that is now used widely in establishing PD models. We, and others, have shown that chronic low dose rotenone treatment induces excessive accumulation of Reactive Oxygen Species (ROS), inclusion body formation and apoptosis in dopaminergic neurons of animal and human origin. Some studies have also suggested that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 66 publications
1
27
0
1
Order By: Relevance
“…The M1 phenotype of microglia was recently reported to be paralleled by a metabolic switch from mitochondrial OXPHOS to glycolysis that enhances carbon flux to the PPP (Figure 1.5) (Gimeno-Bayon et al 2014; Orihuela et al 2016; Voloboueva et al 2013). Interestingly, inhibition of complex I activity activates microglial cells (Shaikh and Nicholson 2009; Ye et al 2016; Yuan et al 2013), while impairment of mitochondrial fission reduces the production of pro-inflammatory signals (Park et al 2013). Induction of the M2-like phenotype results in no observable changes in mitochondrial oxygen consumption or lactate production (Orihuela et al 2016).…”
Section: Mitochondrial Dysfunction In Glial Cells and Its Effect Omentioning
confidence: 99%
“…The M1 phenotype of microglia was recently reported to be paralleled by a metabolic switch from mitochondrial OXPHOS to glycolysis that enhances carbon flux to the PPP (Figure 1.5) (Gimeno-Bayon et al 2014; Orihuela et al 2016; Voloboueva et al 2013). Interestingly, inhibition of complex I activity activates microglial cells (Shaikh and Nicholson 2009; Ye et al 2016; Yuan et al 2013), while impairment of mitochondrial fission reduces the production of pro-inflammatory signals (Park et al 2013). Induction of the M2-like phenotype results in no observable changes in mitochondrial oxygen consumption or lactate production (Orihuela et al 2016).…”
Section: Mitochondrial Dysfunction In Glial Cells and Its Effect Omentioning
confidence: 99%
“…To address this question we analyzed the cells for modulation of Glut-5 and CR3/ 43, two human microglial activation markers, by Western blot (Graeber et al, 1994;Shaikh and Nicholson, 2009). The morphology of the cells was examined daily.…”
Section: Irradiation Causes Activation Of Microgliamentioning
confidence: 99%
“…Recent reports demonstrated that ROS induced by rotenone are involved in dopamine redistribution to the cytosol, whose pro-oxidant conditions might potentiate rotenone-induced apoptosis of dopaminergic cells [182, 194, 195]. Similar to paraquat, rotenone activates microglial cells which might act as an important source for ROS [196]. Although rotenone has represented a useful experimental model of neurotoxicity, it lacks significant specificity for the central nervous system.…”
Section: Molecular Mechanisms Of Paraquat Induced Neurotoxicitymentioning
confidence: 99%